Correction to: Milani, G., Demattè, G., Ferioli, M., Dallagà, G., Lavezzi, S., Basaglia, N., & Straudi, S. (2021). Telerehabiltation in Italy During the COVID-19 Lockdown: A Feasibility and Acceptability Study . International Journal of Telerehabilitation - Ellen R. Cohn (International Journal of Telerehabilitation)
In the metadata for Milani, G., Demattè, G., Ferioli, M., Dallagà, G., Lavezzi, S., Basaglia, N., & Straudi, S. (2021). Telerehabiltation in Italy During the COVID-19 Lockdown: A Feasibility and Acceptability Study . International Journal of Telerehabilitation, 13(1). https://doi.org/10.5195/ijt.2021.6334, acceptability was misspelled in the title (i.e., acceptability) by the journal editor.